KARAKTERISASI KEASAMAN DAN LUAS PERMUKAAN TEMPURUNG KELAPA HIJAU (Cocos nucifera) DAN PEMANFAATANNYA SEBAGAI BIOSORBEN ION Cd2+ - Widihati, I. A. G.; Ratnayani, Oka; Angelina, Yunita (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
The characterization of surface acidity and area of green coconut shell (Cocos nucifera) and the application of the shell as biosorbent of Cd2+ have been conducted in this study. The physico-chemical characterization of the biosorbent was observed by surface acidity measurement using gravimetry, acid base titration, and infrared spectrofotometry, and the surface area was determined by spectrofotometer UV-Vis using methylen blue method. The use of this shell as biosorbent of Cd2+ was studied by the equilibrium time, the adsorption isotherms, the adsorption capacity, and the influence of pH on adsorption capacity. The result showed that the acidity surface of the green coconut shell determined using gravimetric and acid base titration was 39.2647 mmol/g and 39.8843 mmol/g. The surface area was 36.5961 m2/g. The adsorption capacity of green coconut shell (Cocos nucifera) as biosorbent of Cd2+ was 2.5135 mg/g at 4 hours equilibrium time with Cd2+ and initial concentration (adsorption isotherms) of 50 ppm. At pH 11.00 the adsorption capacity of biosorbent on Cd2+ increased to 2.7857 mg/g.
Keywords: green coconut shell (Cocos nucifera), adsorption, Cd2+